The relationship of anxiety and social support with the performance of health workers in the era of the Covid-19 pandemic - Sinuhaji, Lidya Natalia Br (Universitas Aisyah Pringsewu, 2022)
Background: Coronavirus is a large family of viruses that cause illnesses ranging from mild to severe symptoms. Front-line health workers who are directly involved in diagnosing, treating and treating patients with COVID-19 are at risk of developing psychological distress and other mental health symptoms. This study aims: to determine the relationship between anxiety and social support on the work performance of health workers in the COVID-19 pandemic era at the Medan Johor Health Center. The study population: were all health workers in Medan Johor Health Center, totaling 62 health workers and as research subjects. Research type: this is an analytic survey with a cross-sectional research design. Retrieval of data using a questionnaire. The data were processed by univariate analysis using descriptive statistics and bivariate analysis using the Chi-Square test. Results: From the results of the study, it can be seen that from anxiety with the performance of health workers in the era of the COVID-19 pandemic, the results of the Chi-Square test analysis show that the value of p= 0.000 which means less than p= 0.005, it can be concluded that there is a significant relationship between anxiety and the performance of health workers in the era of the COVID-19 pandemic at the Medan Johor Health Center in 2020. And from the research results it can be seen that from social support with performance health workers in the era of the COVID-19 pandemic, namely the results of the Chi-Square test analysis showing that the value of p= 0,000 which means less than p= 0.005, it can be concluded that there is a significant relationship between social support and the performance of health workers in the era of the COVID-19 pandemic. at Medan Johor Health Center 2020.Abstrak: Latar Belakang: Coronavirus merupakan keluarga besar virus yang menyebabkan penyakit mulai dari gejala ringan hingga berat. Tenaga kesehatan garda depan yang terlibat langsung dalam mendiagnosis, merawat, dan merawat pasien COVID-19 berisiko mengalami tekanan psikologis dan gejala kesehatan mental lainnya. Penelitian ini bertujuan: untuk mengetahui hubungan kecemasan dan dukungan sosial terhadap kinerja tenaga kesehatan pada era pandemi COVID-19 di Puskesmas Medan Johor. Populasi penelitian adalah seluruh tenaga kesehatan di Puskesmas Medan Johor yang berjumlah 62 orang tenaga kesehatan dan sebagai subjek penelitian. Jenis penelitian: ini adalah survei analitik dengan desain penelitian cross sectional. Pengambilan data menggunakan kuesioner. Data diolah dengan analisis univariat menggunakan statistik deskriptif dan analisis bivariat menggunakan uji Chi-Square. Hasil: Dari hasil penelitian dapat diketahui bahwa dari kecemasan dengan kinerja tenaga kesehatan di era pandemi COVID-19, hasil analisis uji Chi-Square menunjukkan nilai p= 0,000 yang berarti kurang dari p= 0,005 maka dapat disimpulkan bahwa terdapat hubungan yang signifikan antara kecemasan dengan kinerja tenaga kesehatan pada era pandemi COVID-19 di Puskesmas Medan Johor Tahun 2020. Dan dari hasil penelitian dapat dilihat dari dukungan sosial dengan kinerja tenaga kesehatan di era pandemi COVID-19 yaitu hasil analisis uji Chi-Square menunjukkan nilai p= 0,000 yang artinya kurang dari p= 0,005 maka dapat disimpulkan bahwa ada hubungan yang signifikan antara dukungan sosial dengan kinerja tenaga kesehatan di era pandemi COVID-19. di Puskesmas Medan Johor 2020